Peningkatan Hasil Belajar IPA Materi Perkembangbiakan Hewan dan Tumbuhan Melalui Model Pembelajaran Gallery Walk pada Siswa Sekolah Dasar - Ciptorini Praptiningtyas (Jurnal Pendidikan Dasar, 2020)
Abstract. the general purposes of this research are practicing and analyzing the learning model of Gallery Walk. The specific purpose of this research is improving the class of six from students of 2 Nglangitan Elementary School Scientific result study about the Reproductions of Animals and Plants on the First Semester 2019/2020 Year Academic. This research is going on  the First Semester 2019/2020 Year Academic. The subjects of this research are 20 pupils;consist of 10 boys and 10 girls. The object of this research is the result study about the Reproductions of Animals and Plants. The results of this research are 1) the learning model of Gallery Walk is a learning group with different images media, 2) the learning model of Gallery Walk is focusing on observation to the other groups task result, consist of plot of observation,duration of observation and opportunity of observation, 3) the learning model of Gallery Walk has discussion and correction in equal, 4) the learning model of Gallery Walk is improving the results study optimally. On the Early Condition, the average is 63,75 and the completeness is 55%. On the First Cycle, the average is 73,75 and the completeness is 70%. On the Second Cycle, the average is 86,875 and the completeness is 90%.